Challenges of Nursing Students in Online Synchronous Collaborative Learning Tasks - Narvaez, Roison Andro; Topacio, Ronalyn; Alamo-Lim, Elaine; Verosil Jr., German; Gumabay, Ma. Visitacion (International Journal of Computing Sciences Research, 2023)
Purpose – The goal of this research is to see if the various educational software used in virtual classes helps nursing students learn better. It also tries to discover the difficulties associated with integrating those educational applications into synchronous collaborative group assignments. Method – This study used the descriptive mixed-methods approach, consisting of a survey tool and a qualitative descriptive observation.  A total of 200 nursing students (66 males and 134 women) from different nursing universities in the Philippines took part in this study. Results – The study showed nursing students' difficulties when working in synchronous collaborative assignments in an online learning environment. By and large, the number of obstacles and tactics that each student had to overcome varied. According to nursing students' remarks, the resources available to them, their relationships with professors and classmates, and the school's present online learning regulations and policies all affected their online collaboration challenges and approaches. As a result, they must be viewed as multiple factors interacting. When combined with the pupils' socioeconomic circumstances, the imposed lockdowns worsened the problems were they already suffering due to the pandemic. Conclusion – The findings provided a deeper understanding of the link between learning materials, learners, and learning outcomes in an online learning environment, as well as a multi-perspective on how and why a wholly online learning environment can be successfully implemented. Recommendations – Researchers could go deeper into the topic by interviewing teachers and learning from their viewpoints and experiences to gain a more complete picture of the issue and how distinct components interact with or influence one another. Research Implications  – This study stressed the critical nature of preparation, beginning with the imperative that higher education institutions possess emergency response capabilities and be prepared in the event of another catastrophe. National and institutional policies, procedures, and standards, technical infrastructure and resources, instructional delivery, staff development, potential disparities, and coordination among key stakeholders are just a few of the critical areas that require immediate attention.